STRATEGI KOLABORATIF PENYELENGGARA PEMILU DAN UNIVERSITAS ISLAM DALAM MENANGKAL POLITIK UANG DAN POLITIK IDENTITAS - NADIRSAH HAWARI; AGUSTAM (Politea : Jurnal Politik Islam, 2026)
This study discusses the efforts of election management institutions in creating an educational and collaborative electoral process with UIN Raden Intan Lampung. The research is motivated by concerns among academics and political observers regarding the increasingly pragmatic political climate, often fragmented by symbols of religion, ethnicity, race, and social groups, including in Lampung. The research questions include the legal perspectives on identity politics and vote-buying practices, as well as the collaborative efforts between UIN Raden Intan Lampung and election management institutions to foster a conducive, fair, honest, and dignified democratic atmosphere during the election process, considering that Lampung is one of the provinces prone to vote-buying. This qualitative research employs structured interviews with key figures from the KPUD, Bawaslu, and UIN Raden Intan Lampung, along with field observations. The data is deeply analyzed using ex post facto analysis techniques. The findings reveal that identity politics is still utilized by candidates and their campaign teams to win elections, despite being contrary to election laws and potentially subject to criminal sanctions. The study also finds that UIN Raden Intan Lampung has established tangible collaborative partnerships with election management institutions through sustained cooperation between university leaders, faculties, and study programs, which have positively impacted the development of local democracy in Lampung.